2020
DOI: 10.1002/cb.1857
|View full text |Cite
|
Sign up to set email alerts
|

From corporate environmental responsibility to purchase intention of Chinese buyers: The mediation role of relationship quality

Abstract: Deteriorating environmental conditions and frequent environmental incidents have urged corporations' execution on corporate environmental responsibility (CER). For maintaining a positive CER, buyers have considered the performance of their suppliers' CER when the buyers plan to sign or renew a contract with their suppliers. However, it is still under‐examined how the mechanism works between supplier CER and buyer repurchase intention (BRPI). This study explores the mediating effects of relationship quality bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…In the marketing context, the findings of this study support previous research that explored the roles of producers, retailers and consumers in affecting channel performance [100]. However, the findings of this study demonstrate an irrelevant result to previous studies indicating that satisfaction, trust and commitment, as a subset of relationship quality, have a positive mediating effect on the relationship between corporate environmental responsibility and consumer purchase intentions [16]. Therefore satisfaction, trust, and commitment play an essential role in mediating effect of the retailer-consumer relationship quality on the relationship between producer's environmental performances on consumer's environmental attitudes.…”
Section: Implication To Theorysupporting
confidence: 79%
See 1 more Smart Citation
“…In the marketing context, the findings of this study support previous research that explored the roles of producers, retailers and consumers in affecting channel performance [100]. However, the findings of this study demonstrate an irrelevant result to previous studies indicating that satisfaction, trust and commitment, as a subset of relationship quality, have a positive mediating effect on the relationship between corporate environmental responsibility and consumer purchase intentions [16]. Therefore satisfaction, trust, and commitment play an essential role in mediating effect of the retailer-consumer relationship quality on the relationship between producer's environmental performances on consumer's environmental attitudes.…”
Section: Implication To Theorysupporting
confidence: 79%
“…In the retail environment, the quality of the retailer-consumer relationship plays an essential role in promoting corporate environmental responsibility to encourage consumers' purchase intention [16]. Therefore, consumer attitudes and behavior can benefit retailers to build relationships with consumers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Dash et al (2021) found in event of the perceived value outperforms the buying cost; consumers would be highly satisfied and positively incline toward intention to buy. Similarly, in a related study, Xu et al (2021) argued that satisfied buyers are likely to find their sellers are more reliable and worth an increased commitment to them. Hence, satisfied buyers are likely to have greater intentions to repurchase.…”
Section: The Relationship Between Customer Satisfaction and Purchase ...mentioning
confidence: 93%
“…Therefore, we add the construct of relationship proneness as an exogenous variable in a theoretical model. Previous research has also discussed that customers’ behavioural intentions are influenced by their satisfaction and level of trust in their relationship with the organization (Xu et al., 2021). Consequently, we investigate the role of customer trust in a satisfaction–behavioural intention link.…”
Section: Introductionmentioning
confidence: 99%